Bottom-up assembly of viral replication cycles - Staufer, Oskar; Gantner, Gösta; Platzman, Ilia; Tanner, Klaus; Berger, Imre; Spatz, Joachim P. (Nature Communications, 2022)
Bottom-up synthetic biology provides new means to understand living matter by constructing minimal life-like systems. This principle can also be applied to study infectious diseases. Here we summarize approaches and ethical considerations for the bottom-up assembly of viral replication cycles.
Gesehen am 17.02.2023